Simulation of riding a full suspension bicycle for analyzing comfort and pedaling force - Liu, Y.-S.; Tsay, T.-S.; Chen, C.-P.; Pan, H.-C. (Procedia Engineering, 2013)
Recently, there is an increasing interest on bicycle riding for recreation or fitness purpose. Bicycles are also accepted as urban transportation due to the consciousness of environmental protection. For a more comfortable riding experience, many bicycles are equipped with a suspension system including a front suspension fork and/or rear suspension. However, when a suspension system is added to a bicycle, it makes riding a little heavier since suspension dissipates some pedalling energy. This paper discusses front and rear suspensions corresponding to rider comfort and pedalling effort when riding on a rough road and smooth road. A human body computer model LifeMOD® is employed to model the cyclist. Dynamic analysis software ADAMS® is employed to analyze human body vibration and leg muscle forces of bicycle riding. Human body acceleration vs. vibration frequencies are used as the comfort criteria. The results show that a suspension system may effectively reduce high frequency vibration of the human body when riding on a rough road. Pedalling forces are mostly contributed by the biceps femoris and semitendinosus. The suspension system would increase the pedaling forces of femoris and semitendinosus. Other leg muscles have a minor effect on pedaling forces. Results obtained from this research are useful for the design of bicycle suspension systems with better comfort and less loss of pedalling efficiency.